Analisis Korelasi Antar Parameter QoS: Studi Kasus Kecepatan Data dan Consistency, Serta Hubungan Antara Latency dan Stabilitas Jaringan - Utami, Priska Restu; Kristianti, Veronica Ernita; Afriyenny, Lince (Universitas Gunadarma, 2025)
The growing demand for modern network services, including multimedia applications, real-time communications, and the Internet of Things (IoT), necessitates Quality of Service (QoS) evaluations that extend beyond high data transmission rates to encompass network stability and performance consistency. This study investigates the relationships among QoS parameters, with a particular focus on the correlation between throughput and network consistency, as well as the association between latency and service stability. A quantitative, non-experimental correlational approach was adopted using secondary QoS data derived from the open NordicDat dataset, which reflects real-world network measurements. The analyzed parameters comprise throughput, latency, jitter, and a derived consistency metric computed as an inverse function of jitter. Statistical analyses were performed using descriptive statistics and Pearson and Spearman correlation methods, supported by data visualizations in the form of scatter plots and boxplots. The results reveal that throughput exhibits a strong negative correlation with latency, while demonstrating only a weak positive relationship with network consistency. In contrast, latency and jitter show a more pronounced impact on service stability. The very strong negative association between jitter and consistency confirms that delay variation is a dominant factor in determining network performance stability. These findings indicate that high throughput alone does not ensure network consistency, underscoring the importance of a multidimensional QoS evaluation framework that simultaneously accounts for both transmission speed and stability-related parameters. The outcomes of this study provide valuable insights for the evaluation and design of modern networks that prioritize service quality and sustained performance